2013
DOI: 10.1144/jgs2012-008
|View full text |Cite
|
Sign up to set email alerts
|

The role of strain localization in magma injection into a transtensional shear zone (Variscan belt, SW Iberia)

Abstract: This study deals with the interaction between deformation and magmatism in mid- to deep-crustal domains. The relation is analysed between migmatites and shear zones and the spatial distribution of leucogranitoid veins and dykes running through a footwall migmatite system, and reaching a transtensional shear zone operated under amphibolite- to greenschist-facies metamorphic conditions (Boa Fé shear zone, Variscan belt, SW Iberia). Statistical results show that the frequency of width and spacing of the leucogran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The high-T/low-P deformation affected syn-orogenic granitoids (peraluminous granodiorite-granite suite) and previous folds, and was parted into subhorizontal and strike-slip shear zones parallel or subparallel to the structural trend of the orogen (Díaz Azpiroz et al, 2004;Pereira et al, 2009Pereira et al, , 2012bPereira et al, , 2013. On the other hand, the Iberian Allochthon displays a number of low-angle normal faults that cut previous faults and folds (Azor et al, 1994b;Expósito et al, 2002).…”
Section: Sw Iberian Allochthon and Autochthonmentioning
confidence: 99%
“…The high-T/low-P deformation affected syn-orogenic granitoids (peraluminous granodiorite-granite suite) and previous folds, and was parted into subhorizontal and strike-slip shear zones parallel or subparallel to the structural trend of the orogen (Díaz Azpiroz et al, 2004;Pereira et al, 2009Pereira et al, , 2012bPereira et al, , 2013. On the other hand, the Iberian Allochthon displays a number of low-angle normal faults that cut previous faults and folds (Azor et al, 1994b;Expósito et al, 2002).…”
Section: Sw Iberian Allochthon and Autochthonmentioning
confidence: 99%
“…Transpressional deformation during magmatism has been proposed to be important for the mobilization of magma through the continental crust (Weinberg et al, 2004;Marcotte et al, 2005;Whitney et al, 2009;Pereira et al, 2013). Other workers, however, have suggested that changes in the thermal gradient of country rocks dominantly control magma transport (Vigneresse, 1995;Johnson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other workers, however, have suggested that changes in the thermal gradient of country rocks dominantly control magma transport (Vigneresse, 1995;Johnson, 2009). The interplay between pluton emplacement and transpression at different crustal levels is still poorly understood; consequently, an enhanced understanding of the way(s) in which magma is transferred and emplaced within continental arcs during periods of regional deformation can elucidate a fundamental question in the evolution of continental crust and magmatic arc systems (e.g., Paterson et al, 1998;Paterson and Schmidt, 1999;Blanquat et al, 1998;Vigneresse and Clemens, 2000;Pereira et al, 2013;Bitencourt and Nardi, 2000;Sen et al, 2014;Webber et al, 2015;Stuart et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3-7, 9 and 12), following several previous studies that have proposed that high-strain zones (shear and tension zones) could play a significant role in the draining of residual fluids from deeper retention zones at the strain rate of 10 −15 s −1 to ∼10 −10 s −1 indicated by structure (Fernández and Castro, 1999), analogue (Benn et al, 1998) and numerical models (Cruden, 1998;Berdiel et al, 1997), feeding the upper crust with partially molten lower crustal rocks (Fossen and Tikoff, 1998;Neves et al, 1996Neves et al, , 2000Pereira et al, 2013;Snoke et al, 1999;Weinberg et al, 2006).…”
Section: Strain and Reliefmentioning
confidence: 91%